DEVELOPMENT OF SPENT CHICKEN MEAT SPREAD INCORPORATING POULTRY LIVE - P. Poobal; V.N. Vasudevan; P. Kuttinarayanan; T. Sathu; K. Vrinda Menon (Journal of Veterinary and Animal Sciences, 2017)
The present study was carried out to develop spent chicken meat spread incorporating edible poultry offal. Three different treatments were carried out with 5 (T1), 10 (T2) and 15 (T3 ) per cent incorporation of chicken liver along with cooked cured spent chicken meat and other non-meat ingredients. The optimumblevel of incorporation of liver was determined by sensory evaluation of the fresh product. Chicken meat spread incorporated with 5 perncent chicken liver (T1 ) had significantly higher overall acceptability score than that of T2 and T3. Moreover, T1 had the highest appearance, flavour, spreadability, aftertaste and adhesive ability scores among the three treatment groups. The current study has standardized the development of a spent chicken meat spread with five per cent added chicken liver which had desirable sensory attributes. Further studies are needed to assess the composition and shelf life of the developed product.